Interim management: A 21st century model of professionalism? - Farkas, Ferencné; Magyari, Éva (The Hungarian Journal of Marketing and Management, 2019)
This paper tends to introduce interim management, which is a new phenomenon in Hungary. To understand the establishment of this field of management our aim was to create knowledge by analysing the international literature, empirical researches and observations. Having defined interim management, we examine the working mechanism, development and market characteristics of interim management afterwards we discuss the motivations of interim managers, the lifestyle of them and the necessary competencies.